2022
DOI: 10.1002/aocs.12674
|View full text |Cite
|
Sign up to set email alerts
|

Muffins made with monoglyceride oleogels: Impact of fat replacement on sensory properties and fatty acid profile

Abstract: Most shortenings used in baked products are solid fats high in saturated fatty acids that may also contain trans fatty acids, which are nutritionally unhealthy. Successful solid fat replacement requires maintaining not only the physicochemical properties, but also the sensory quality of the products. In this study, the sensory properties and lipid profile of muffins formulated with a previously optimized monoglyceride oleogel were compared with those of muffins made with a commercial margarine (Control). Untra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The suggested model and LOF should, respectively, be significant (p value ≤ 0.05) and insignificant. The difference between predicted- R2 and adjusted- R2 shouldn't be greater than 0.2 and AP value greater than 4 is preferable [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…The suggested model and LOF should, respectively, be significant (p value ≤ 0.05) and insignificant. The difference between predicted- R2 and adjusted- R2 shouldn't be greater than 0.2 and AP value greater than 4 is preferable [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…In this regard, many researchers focus on bakery products to reduce shortening content. Giacomozzi et al, 2023 made muffins with monoglyceride oleogels achieved similar results as commercial margarine, and Pehlivanoglu et al, 2018 used oleogels with different oils rich in unsaturated fatty acid as a shortening replacer in cake concluded that oleogel cakes obtained sensory scores close to the control sample. However, studies on applying oleogels prepared with different oil mixtures replaced with solid fats in aerated foods are still lacking.…”
Section: Introductionmentioning
confidence: 90%
“…Furthermore, muffins have been produced with MAG oleogel from HOSO [ 26 , 77 ]. In the formulation of muffins, conventional margarine was swapped out for the optimized oleogels, resulting in items with improved spreadability, increased specific volume, comparable toughness values, and a more linked and uniform crumb structure.…”
Section: Application Of Oleogel In the Food Industrymentioning
confidence: 99%
“…In addition, the reformulated muffins exhibited a considerably better lipid profile, with a 68% decrease in SFA and an almost four times increase in monounsaturated fats. Our findings suggest that muffins made with oleogel might be suitable for introducing customers to a new product with a healthy fatty acid composition [ 77 ].…”
Section: Application Of Oleogel In the Food Industrymentioning
confidence: 99%